Some considerations on functional surgery in gynecology - Wood, Juan (2015)
More than five decades ago gynecological therapeutic been following a decidedly conservative orientation or more properly functional, thinking that informs especially the surgical technique, so that, apart from malignancies, gynecologists, at least among us, try as far as possible to respect or restore sexual function in its entirety. Reasons supporting this trend are obvious and, therefore, it is unnecessary to expose.